Pengaruh Student Company Terhadap Kompetensi Kewirausahaan Siswa Sekolah Menengah Kejuruan Di Daerah Istimewa Yogyakarta - Sulasmi Sulasmi; Moerdiyanto Moerdiyanto (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
The purpose of the research is to describe Student Company program and its effect on entrepreneurial competencies of vocational high school students in Yogyakarta. This research is expost facto study. The research was conducted at SMK 1 Depok, SMK 2Depok, SMK 1 Godean, SMK 7 Yogyakarta and SMK 1 Seyegan. Data collection techniques were questionnaires and observation. The data was analyzed using descriptive analysis and multiple linear regression. The results of this study were: (1) Student company was effective to improve the entrepreneurship competencies of vocational high school students in Yogyakarta. The effectiveness of planning aspects was in excellent category (42.11%), the implementation aspects was in the good category (35.79%), and the effectiveness of the controls was in the good category (48.42%). (2) Entrepreneurship competencies of students who took SC were in the good category (56.84%). (3) The planning aspect of student company has significant effect on the entrepreneurship competencies of students (t=2.954;Sig= 0.004). (4) The implementation aspects have significant effect on the entrepreneurship competencies of students (t= 3.627;Sig=0.000). (5) The control aspect does not have significant effect on the entrepreneurship competencies of students (t=0.573;Sig=0.568). (6) The aspects of planning, implementation, and control simultaneously have a significant effects on the entrepreneurship competence of vocational high school students in Yogyakarta (F=8.755;Sig =0.000).